Fremdheit und Vertrautheit: Hermeneutik im europäischen Kontext : [der vorliegende Band dokumentiert den internationalen Kongreß, der im September 1994 unter dem Titel "Fremdheit und Vertrautheit. Hermeneutik im europäischen Kontext" an der Martin Luther-Universität Halle-Wittenberg stattgefunden hat] - Adriaanse, Hendrik J.; Enskat, Rainer; Adriaanse, Hendrik J. (Peeters, 2000)
The present volume contains the lectures and papers given at the 1994 international conference on hermeneutics in Halle (Germany). The conference aimed at a state of the art in the light of recent developments in science and humanities. The place in which the conference was held is renowned for its centuries-old tradition in hermeneutics and among the lectures there are indeed some devoted to this history. For the most part, however, the papers concentrate on present-day problems in fields as different as comparative literature, religious studies, bible exegesis, esthetics, social sciences, intercultural dialogue. The theme of the conference, "strangeness and familiarity", reflects the tension in which any interpretation process is situated and that any theory of interpretation has to account for. The contributions to the volume are in German and French.